AN ANALYSIS OF MECHANICAL PROPERTIES OF HADFILED STEEL AFTER SOLUTION ANNEALING, SOLUTION ANNEALING WITH TEMPERING AND REPETITIVE HAMMERING - Farida, Ida
Hadfield steel is steel which contains Mn 11-14% and C 1.1-1.4%. This study aims to analyze the mechanical properties of hadfield steel after the heat treatment process (solution annealing, normalizing, tempering) and after the heat treatment process (solution annealing, tempering) followed by strain hardening with repetitive hammmering method. Hadfiled steel which undergone a heat treatment process showed insignificant difference in terms of microstructure and hardness value. On the other hand, the hadfield steel which was given the heat treatment and combined with repetitive hammering showed a change in terms of microstructure, which is indicated by the presence of increasing and a more compact slip line, in accordance with the more amount of given deformation, for the hardness value of hadfield steel also indicates a significant increasing. As for the slip line discovered in hadfiled steel, which undergone a solution annealing and tempering process followed by repetitive hammering, have increased in a number and appears more compact compare to hadfield steel without tempering process. Also, the hardness value of hadfield steel with tempering process is higher than hadfiled steel without tempering process. The results of strain values and thick reduction exihibited that Hadfield steel through a tempering process has a higher strain value and a thick reduction value than hadfield steel without the tempering process. High strain values and high reduction values result in high hardness values.